The Sociology of hate speech - Bajt, Veronika (Annales. Series historia et sociologia, 2025)
Hate speech reflects and reinforces underlying prejudices and structural inequalities, functioning as a mechanism to maintain existing power dynamics and social hierarchies. It is a multifaceted sociological phenomenon that intersects with the multileveled concepts of nationalism, racism, gender, and migration. This article argues that a comprehensive understanding of these intersections is necessary to sociologically analyse hate speech, revealing this interplay between systemic power structures and individual prejudices. This is necessary if we are to understand and mitigate the rising influence of hate speech in society.
Keywords: border; confine; čistost; discorso d’odio; hate speech; meja; migracija; migration; migrazione; nacionalizem; nationalism; nazionalismo; purezza; purity; sovražni govor